Phylogenetic relationship among some cultivars of date palm (Phoenix dactylifera L.) on the basis of flavonoid spectrum (Indian Journal of Arid Horticulture, 2025)
In order to develop phyto-chemical markers for delimitation of date palm cultivars, a study was undertaken using five cultivars. The foliar flavonoids were extracted and separated on TLC plates coated with cellulose. The spots thus developed were compared and subjected to cluster analysis using computer software. The results demonstrated that date palm cultivars can be identified using either specific spot or spot combinations. The results of the cluster analysis demon- strated that the selected five cultivars can be grouped into three distinct groups on the basis of their genetic distances. The group A was represented by cultivars Khuneizi and Dayari were has closer affinity with Halawy. The Group B1 was repre- sented by Sewi and the group B2 by cvs. Khuneizi, Dayari and Halawy.
Keywords: Date palm; Phoenix dactylifera; Phylogeny; flavonoid; TLC